Pharmacologic downregulation of protein arginine methyltransferase1 expression by adenosine dialdehyde increases cell senescence in breast cancer - Singh, Priya; Charles, Soniya; Madhavan, Thirumurthy; Munusamy-Ramanujam, Ganesh; Saraswathi, Nambiappan T.; Arasu, Mariadhas Valan; Al-Dhabi, Naif Abdullah; Arshad, Aziz; Arockiaraj, Jesu; Mala, Kanchana (Elsevier BV, 2020)
We investigated the role of protein arginine methylation (PAM) in estrogen receptor (ER)-positive breast cancer cells through pharmacological intervention. Tamoxifen (TAM) or adenosine dialdehyde (ADOX), independently, triggered cell cycle arrest and down-regulated PAM, as reduced protein arginine methyltransferase1 (PRMT1) mRNA and asymmetric dimethylarginine (ADMA) levels. Synergistic effect of these compounds elicited potent anti-cancer effect. However, reduction in ADMA was not proportionate with the compound-induced down-regulation of PRMT1 mRNA. We hypothesized that the disproportionate effect is due to the influence of the compounds on other methyltransferases, which catalyze the arginine dimethylation reaction and the diversity in the degree of drug-protein interaction among these methyltransferases. In silico analyses revealed that independently, ADOX or TAM, binds with phosphatidylethanolamine-methyltransferase (PEMT) or betaine homocysteine-methyl transferase (BHMT); and that the binding affinity of ADOX with PEMT or BHMT is prominent than TAM. These observations suggest that in breast cancer, synergistic effect of ADOX + TAM elicits impressive protective function by regulating PAM; and plausibly, restoration of normal enzyme activities of methyltransferases catalyzing arginine dimethylation could have clinical benefits.